Design of Remote Control Juvenile Healthy Smart Pillow - Huadong Zhou; Xuran He; Jiaheng Yang; Lifan Liao (Institute of Advanced Engineering and Science, 2017)
High-quality modern life results in many unique diseases of modern people, cervical spondylosis, sleep disorders. Adolescents lack of sleep have a negative impac on the students themselvest. Not only it will reduce the body resistance, prone to a variety of diseases, but also it make learning when the spirit is not concentrated, attention is decreased, thus affecting the learning state. Long-term lack of sleep will lead to psychological problems, a potential threat is formed to the physical and mental health of young people. To this end, based on WeChat platform, a young people's health intelligence pillow is designed, it can be remotely controned.